Survival analysis model to estimate sensory shelf life with temperature and illumination as accelerating factors - Garitta, Lorena; Langohr, Klaus; Elizagoyen, Eliana; Gugole Ottaviano, Fernanda; Gómez, Guadalupe; Hough, Guillermo (Food quality and preference, 2018)
•We developed a survival model which considered two accelerating factors: temperature and illumination.•The blocking effect of the consumer was considered in the survival model.•The model was applied to real data from a lemon-flavored drink sensory shelf-life.•As expected shelf life was shortened with an increase in temperature and under illumination. The main objective of this study was to introduce a survival model to contemplate two simultaneous accelerating factors affecting a food product’s shelf life: temperature and illumination. A second objective was to consider the case where the same consumer tests different experimental conditions and thus his/her data are not independent. Sample data comprised 108 consumers who evaluated a lemon-flavored juice stored at 24 °C, 37 °C and 45 °C; under conditions of no-illumination and with illumination; with seven different storage times for each of the six experimental conditions. Aiming to estimate the storage time at which a consumer rejects a sample a model including an Arrhenius term for the temperature, a binomial response for illumination (with and without) and the interaction of both was developed. The model also considered that the same consumer tested different experimental conditions.